Modelling uncertainty and response styles in ordinal data. (15th April 2018) - Simone, Rosaria; Tutz, Gerhard
Abstract : Mixture models for ordinal responses in the tradition ofcub models use the uniform distribution to account for uncertainty of respondents. A model is proposed that uses more flexible distributions in the uncertainty component: the discretized Beta distribution allows to account for response styles, in particular the preference for middle or extreme categories. The proposal is compared with traditionalcub models in simulation studies and its use is illustrated by two applications.